ENVIRONMENTALLY FRIENDLY VILLAGE (ADVOCATION PROGRAM AND WASTE MANAGEMENT IN ECONOMIC DEVELOPMENT RW 01 BABALAN LOR, BOJONG, PEKALONGAN) - Tarmidzi; Abdul Aziz; Muh. Izza (Islamic Studies Journal for Social Transformation, 2017)
Living creatures produce waste everyday. Its management must be taken seriously from now or else it can be national disaster. Government needs other parties to hand in hand handling waste problem. As an institution with a community service duty, IAIN Pekalongan views waste management to be part of its responsibilities. Using participative action research with participative observation, interview, documentation, and focus group discussion as data collection instruments, a planned action was set up. A team of community service of IAIN Pekalongan along with members of community performed a mentoring program to optimalize the waste bank, Berkah Mulya, through delevoping a Shared Community Business Group (KUMB), which comprises to several KSM. Through trainings, facilitation, mentoring, and consultation, KUMB and KSM have well developed. The products resulted from these activities are handycrafts made from household waste, optimalization of yard, and diversification of tofu waste. RW01 Desa Babalanlor through this program has become a pioneer of tour destination of educative village Kampung Tahu Ramah Lingkungan.